Assessment of heavy metal and As contamination in the surface sediments of Po delta lagoons (Italy). (30th September 2019) - Zonta, Roberto; Cassin, Daniele; Pini, Roberto; Dominik, Janusz
Abstract: The River Po, Italy's most important watercourse (650 km long, 71, 000 km 2 surface area, 1500 m 3 /s average discharge), flows into the Adriatic Sea forming a large Delta (180 km 2 ), within which lie a dozen lagoons of varying morphological and hydrodynamic characteristics. In contrast to the wide variety of studies of the River, its Delta and its Prodelta carried out in the last few decades, and despite the value of the lagoons in ecological, cultural and economic (tourism, aquaculture) terms, heavy metal contamination in the Po Delta lagoons has not been extensively studied. The surface sediments (0–6 cm depth) of the seven main Delta lagoons were investigated, analysing grain size, organic and inorganic carbon and major (Al, Fe, Mn) and trace (As, Cd, Cr, Cu, Hg, Li, Ni, Pb, Zn) element concentrations in 24 sites. The suspended loads of the River Po distributaries, delivered to the lagoons either directly or via coastal transport processes (coastal currents, tides, resuspension), and the sedimentary environment inside the lagoons (internal currents, water renewal times) were the main determinants of sediment texture. Three grain-size distribution types, identified by cluster analyses and parameterised by the percentage of fine particles (d < 16 μm), strongly influenced the concentrations of some trace elements (Cu, Pb, Zn), while others were less dependent on grain-size distribution (As, Cr, Hg, Ni). Nickel was the only metal with potentially dangerous levels in the Delta lagoon sediments, exceeding the Effect Range-Median limit in 83% of sites. Despite being mainly of geogenic origin, Ni may be of ecotoxicological concern due to its potential mobility, as indicated by two weak selective extractions. Specifically, extraction of the reducible phase (Mn and Fe oxy-hydroxides) released on average 45% of total Ni content. Changes in redox conditions as a consequence of hypoxia/anoxia episodes in the Po Delta lagoons may thus induce Ni release from sediments. Highlights: Sediment grain-size and metal distributions in the Po Delta lagoons (Italy). Sediment texture typology and metal contamination level. Important fraction of Ni can be released under anoxic conditions. Ni concentrations in surface sediment are potentially harmful for aquatic life. Other metal concentrations are well below levels of potential toxicological risk.